TL1A serves as a positive regulator to promote adipocyte differentiation - Ziqi Chang; Qiaoyu Wang; Yan Zhai; Ke Li; Xianjie Zheng; Yaohui Wang; Dan Zhao (PLoS ONE, 2026)
Adipogenesis, the intricate process of differentiation from preadipocytes or mesenchymal stem cells into mature adipocytes, is crucial for the formation and metabolic function of adipose tissues in mammals. The TNF ligand–related molecule 1A (TL1A) is a type II transmembrane protein belonging to the TNF superfamily. Inflammation is involved in the whole process of adipocyte cell formation and obesity development. To investigate the potential influence of TL1A on adipocyte development, we examined mouse embryo fibroblasts (MEFs) and 3T3-L1 cells. Our findings indicated that TL1A-treated MEFs exhibited an elevated rate of spontaneous adipogenesis, with a significant enhancement in adipocyte formation upon induction with a combination of insulin, dexamethasone and methylisobutylxanthine. This increased adipogenesis was evidenced by augmented lipid droplet formation and elevated expression of several adipogenic markers. Specifically, there was an upregulation of early-stage adipogenesis genes, including Krox20, KLF5, C/EBPβ and C/EBPδ, as well as late-stage adipogenesis regulators such as KLF15, C/EBPα, PPARγ and aP2. Moreover, TL1A significantly upregulated the protein expression of adipogenic markers (C/EBPα, C/EBPβ, PPARγ, CD36 and aP2) in MEFs and 3T3-L1 cells. Mechanistically, TL1A enhanced the phosphorylation of yes-associated protein 1 (YAP1), which led to cytoplasmic retention. Ultimately, TL1A inhibited the stabilization and nuclear transfer of β-catenin in MEFs, probably through regulating the upstream protein YAP1. Taken together, TL1A promoted adipogenic differentiation of MEFs and 3T3-L1 cells in vitro, which partly via inhibiting YAP1 mediated β-catenin signaling pathway.